2020
DOI: 10.3390/ijerph17051773
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of Vibration Perception Threshold Test in People with Type 2 Diabetes Mellitus

Abstract: Background: Diabetes mellitus is a chronic disease characterized by fasting hyperglycemia. It affects approximately 415 million people worldwide and involves a variety of complications. One of them is the loss of sensitivity to peripheral vibration. Objective: Our study aims to discover the test-retest reliability of a procedure for assessing vibration sensitivity in people with type 2 diabetes mellitus. Methodology: 90 people with type 2 diabetes mellitus (56 men and 34 women) performed the vibration percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…In our study, the VPT value showed a strong correlation with the composite score of NCS reflecting DPN severity. As a higher VPT value is associated with balance and fear of falling, this convenient [ 19 ] and reliable [ 21 ] quantitative assessment may represent a useful addition to the standardized evaluation of patients with type 2 DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the VPT value showed a strong correlation with the composite score of NCS reflecting DPN severity. As a higher VPT value is associated with balance and fear of falling, this convenient [ 19 ] and reliable [ 21 ] quantitative assessment may represent a useful addition to the standardized evaluation of patients with type 2 DM.…”
Section: Discussionmentioning
confidence: 99%
“…DPN can be assessed in several ways using different types of symptom scores and several kinds of measurements [ 18 ]. The vibration perception threshold (VPT) with a quantitative sensory testing (QST) approach was demonstrated to be a useful screening tool in many studies [ 19 , 20 , 21 , 22 ]. Because vibration sense is often impaired in large myelinated nerve fiber deficits such as in DPN, the VPT is widely used for screening for large fiber function in DM [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vibration units can be calculated by the following equation: A = x 2 /2 where x is the vibration unit (vu) and A is the amplitude expressed in microns (μ). This instrument has shown excellent reliability in patients with T2DM [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“… 22 , 23 , 24 Test-retest reliability has been reported in various populations, including adults with low back pain 25 and diabetes. 26 The Vibratron II includes a controller and a vibrating transducer (120Hz) with a 1-cm post. The control unit allows vibration amplitude modulation from 0.0 to 20.0 vibration units (0.1 vibration unit=0.005 microns; 20.0 vibration units=200 microns).…”
Section: Methodsmentioning
confidence: 99%